2014
DOI: 10.2105/ajph.2013.301749
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Suicidality Among Racially/Ethnically Diverse Sexual Minority Youths

Abstract: Objectives We examined the relationships among sexual minority status, sex, and mental health and suicidality, in a racially/ethnically diverse sample of adolescents. Methods Using pooled data from 2005 and 2007 Youth Risk Behavior Surveys, hierarchical linear modeling was used to examine 6 mental health outcomes across 6 racial/ethnic groups, intersecting with sexual minority status and sex. Based on an omnibus measure of sexual minority status, there were 6,245 sexual minority adolescents in the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
139
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(157 citation statements)
references
References 26 publications
(33 reference statements)
12
139
3
Order By: Relevance
“…National surveys of adolescent health, such as the YRBS, should recognize the importance of including sexual orientation and attraction in survey instruments to improve the ability to develop effective suicide and bullying prevention programs for sexual minority youths. Furthermore, our research, along with other recent research, 37,38 showed the advantage of using an intersectional perspective to understand mental health disparities. Finally, school personnel should develop antibullying and antihomophobia policies in response to the disproportionate risk of being bullied and reporting suicidality among sexual minority youths.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…National surveys of adolescent health, such as the YRBS, should recognize the importance of including sexual orientation and attraction in survey instruments to improve the ability to develop effective suicide and bullying prevention programs for sexual minority youths. Furthermore, our research, along with other recent research, 37,38 showed the advantage of using an intersectional perspective to understand mental health disparities. Finally, school personnel should develop antibullying and antihomophobia policies in response to the disproportionate risk of being bullied and reporting suicidality among sexual minority youths.…”
Section: Discussionmentioning
confidence: 53%
“…Other research, which compared sexual minorities of different races/ ethnicities and genders with one another, found very few differences in terms of their risk for suicidality. 37 Taken together, these findings suggest that regardless of race/ethnicity or gender, sexual minorities are more vulnerable to poor mental health outcomes than are sexual majorities. It is also interesting to note that when we compared Black and Hispanic heterosexual youths with their same-gender White heterosexual peers, the racial differences in reporting suicide ideation were not statistically significant.…”
Section: Discussionmentioning
confidence: 90%
“…48 Pinhey and Millman found that same-sex orientation was associated with a greater risk of suicide attempt among students in Guam. 49 …”
Section: Question 1: What Do We Know About Risk and Protective Factormentioning
confidence: 98%
“…12-13). Savin-Williams [2016] points the reader to some sources for this claim in the notes section at the back of the book, but he fails to acknowledge the numerous studies that have continued to document health and mental health disparities between heterosexual and sexual minority youth [e.g., Bostwick et al, 2014;Marshal et al, 2011;Robinson & Espelage, 2013; for a review, see Russell & Fish, 2016]. Being a critical consumer of all of this research, I felt uncomfortable with the lack of recognition of other evidence or the acknowledgment that the question of psychological "equivalence" versus "distinction" may be unsettled in the larger scientific community.…”
Section: A Note On Genre and Data Corpusmentioning
confidence: 99%